Computational advancement in communication circuits and systems proceedings of ICCACCS 2014 - Maharatna, Koushik; Dalapati, Goutam Kumar; Banerjee, P K; Mallick, Amiya Kumar; Mukherjee, Moumita (Springer India, 2015)
This book comprises the proceedings of 1st International Conference on Computational Advancement in Communication Circuits and Systems (ICCACCS 2014) organized by Narula Institute of Technology under the patronage of JIS group, affiliated to West Bengal University of Technology. The conference was supported by Technical Education Quality Improvement Program (TEQIP), New Delhi, India and had technical collaboration with IEEE Kolkata Section, along with publication partner by Springer. The book contains 62 refereed papers that aim to highlight new theoretical and experimental findings in the field of Electronics and communication engineering including interdisciplinary fields like Advanced Computing, Pattern Recognition and Analysis, Signal and Image Processing. The proceedings cover the principles, techniques and applications in microwave & devices, communication & networking, signal & image processing, and computations & mathematics & control. The proceedings reflect the conference?s emphasis on strong methodological approaches and focus on applications within the domain of Computational Advancement in Communication Circuits and Systems. The content also emphasizes the emerging technologies in the Electronics and Communication field together in close examinations of practices, problems and trends.